(H)IM Scansione libera tutti – flussi open per la gestione della realtà complessa (GEOmedia, 2020)
The study of the archaeological site of the ancient Roman houses on Celio we have analyzed how it is possible to use Open Source products and workflow to manage data of reality up to the Bim modeling. Assuming that heritage is a world of construction more tied to creativity, organic forms, and dynamismrather than industrialization. Is it possible today to have data management not dependent on authoring systems? Key of the process not the simplified or translated information model, but the real model detected, the digital twin. Open data input to keep all the necessary information about building.